2020
DOI: 10.1080/19490976.2020.1774311
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy aggravates DNA damage response and gastric tumorigenesis via Rad51 ubiquitination in response to H. pylori infection

Abstract: Helicobacter pylori (H. pylori) infection is the strongest known risk factor for the development of gastric cancer. DNA damage response (DDR) and autophagy play key roles in tumorigenic transformation. However, it remains unclear how H. pylori modulate DDR and autophagy in gastric carcinogenesis. Here we report that H. pylori infection promotes DNA damage via suppression of Rad51 expression through inhibition of autophagy and accumulation of p62 in gastric carcinogenesis. We find that H. pylori activated DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…Our data showed that DCTPP1 silencing triggers DNA damage in BRCA cells, while its upregulation up-regulated the levels of DNA repair-associated factors, XRCC1, PARP1, and RAD51. DNA repair pathways are DNA damage response mechanisms ( 28 , 29 ). DNA repair pathways influence cell survival and are anti-cancer therapeutic targets of radiotherapy and cytotoxic chemotherapy ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that DCTPP1 silencing triggers DNA damage in BRCA cells, while its upregulation up-regulated the levels of DNA repair-associated factors, XRCC1, PARP1, and RAD51. DNA repair pathways are DNA damage response mechanisms ( 28 , 29 ). DNA repair pathways influence cell survival and are anti-cancer therapeutic targets of radiotherapy and cytotoxic chemotherapy ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In protein–protein interactions, one study suggested that the relationship between RAD51 and autophagy is associated with checkpoint kinase 1 (CHK1) in an esophageal cancer model by inhibiting autophagy [ 22 ]. Thus, in several cancers, the inhibition of autophagy promotes DNA damage and a susceptibility to cancer treatment by the downregulation of RAD51 [ 23 , 24 , 25 ]. On the contrary, one study reported that inducing autophagy reduces RAD51 expression in non-small cell lung cancer (NSCLC) cell models [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of them (e.g., Flavonifractor , Enterorhabdus , Desulfovibrio , Elusimicrobium , Roseburia , Candidatus _ Saccharimonas , Anaerovorax , Caproiciproducens , Lachnoclostridium , Ruminiclostridium , Intestinimonas ) play a key role in immunity regulation and intestinal health ( Zhang et al, 2020a ; Zhang et al, 2020b ; Zhao, Jiang & Chu, 2020 ; Ward et al, 2017 ; Zhang et al, 2020a ; Zhang et al, 2020b ). However, Unidentified_Clostridiales , Oscillibacter , Anaerofilum , Parasutterella , Tyzzerella , Blautia , Peptococcus , Mycoplasma , Helicobacter , Butyricimonas have pathogenic and pro-inflammatory effects ( Xu et al, 2020 ; Xue et al, 2020 ; Xie et al, 2020 ). The change in their abundance of these bacteria with age may be a potential reason for the shorter life span (around one year) of Brandt’s voles in the wild.…”
Section: Discussionmentioning
confidence: 99%